Expansion of Brycon dentex (Characiformes: Characidae) and Hamuelopsis elongatus (Perciformes: Heamulidae) distribution in Ecuador - Jonathan Valdiviezo Rivera (ACI Avances en Ciencias e Ingenierías, 2014)
The fishes Brycon dentex and Hamuelopsis elongatus were collected for the first time in the Santiago-Cayapas ictiohidrographic zone, at the Mira and Camumbi rivers, River Mira basin, Tobar Donoso area, province of Carchi, Ecuador. Previous records of the species were from the Esmeraldas and Intertidal ictiohidrographic zones, respectively.